Enhancing open-circuit voltage in gradient organic solar cells by rectifying thermalization losses - Andersson, Olof; Kemerink, Martijn (Solar RRL, 2020)
In virtually all solar cells, including optimized ones that operate close to the Shockley-Queisser (SQ) limit, thermalization losses are a major, efficiency-limiting factor. In typical bulk heterojunction organic solar cells, the loss of the excess energy of photocreated charge carriers in the disorder-broadened density of states is a relatively slow process that for commonly encountered disorder values takes longer than the charge extraction time. Herein, it is demonstrated by numerical modeling that this slow relaxation can be rectified by means of a linear gradient in the donor:acceptor ratio between anode and cathode. For experimentally relevant parameters, open-circuit voltage (VOC) enhancements up to ≈0.2 V in combination with significant enhancements in fill factor as compared to devices without gradient are found. The VOC enhancement can be understood in terms of a simple nonequilibrium effective temperature model. Implications for existing and future organic photovoltaics (OPV) devices are discussed.